A Review Of Three Aspects Successful Business Digitalization: Marketing, Finance, And Service - Ainun Is Yuni Zafirah; Helma Renanda Yuniartika Putri; Nurul Badriyah; Siti Sri Wulandari; Yessy Artanti (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to explore the extent to which digitalization can provide benefits for business actors and satisfaction for customers or consumers as well as the obstacles faced by business actors from technological developments. With a literature study approach, this study analyzed 27 scientific articles indexed in SINTA and SCOPUS. The method applied is content analysis of relevant literature to identify the contribution of digitalization to three important aspects (marketing, finance, and services), as well as the obstacles faced by business actors in the process of digitalization business transformation. The results of the study show that digitalization in marketing allows companies to reach wider consumers, increase the effectiveness of promotional strategies, and strengthen relationships with customers. In terms of finance, digitalization supports transaction efficiency and facilitates data-based decision making. On the service side, digitalization contributes to increasing customer satisfaction through automation and faster response. However, business actors are also faced with various challenges that can be grouped into three factors based on the TOE framework (Technology, Organizational, and Environmental).